2022
DOI: 10.3389/fpsyg.2022.830716
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Green Intellectual Capital on Green Innovation: A Green Supply Chain Integration Perspective

Abstract: To demonstrate how green innovation (GI) effectively occurs, this study examines the effects of green intellectual capital (GIC) on GI from the perspective of green supply chain integration (GSCI). Based on a natural-resource-based view and knowledge-based view, the authors constructed an intermediary model of GIC-GSCI-GI, and analyzed the effects of green absorptive ability (GAA) and relationship learning ability (RLA) as moderators. An empirical survey of 328 Chinese manufacturing companies was conducted. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The resource-based view addresses the complexity of organizing a business by emphasizing the importance of investing significant effort in developing, maintaining, and effectively utilizing the resources and capabilities that are essential for the firm's success [19]. Liu et al (2022) [20] examined the impact of green process innovation, green innovation strategy, and green action innovation on sustainable performance, using the theoretical framework of a resource-based view. They also explored the moderating effects of green product innovation and employees' green behavior.…”
Section: Literature Review and Hypothesis Development 21 Theoretical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The resource-based view addresses the complexity of organizing a business by emphasizing the importance of investing significant effort in developing, maintaining, and effectively utilizing the resources and capabilities that are essential for the firm's success [19]. Liu et al (2022) [20] examined the impact of green process innovation, green innovation strategy, and green action innovation on sustainable performance, using the theoretical framework of a resource-based view. They also explored the moderating effects of green product innovation and employees' green behavior.…”
Section: Literature Review and Hypothesis Development 21 Theoretical ...mentioning
confidence: 99%
“…That study was based on a holistic resource-based view, which was supported by stakeholder and contingency mechanisms. Liu et al (2022) [20], constructed an intermediate model between green intellectual capital, green supply chain integration, and green innovation, based on a natural resource-based perspective and a knowledge-based perspective, and analyzed the effects of green absorptive capacity and relational learning capacity as moderators. Adam et al (2022) [23] examined the use of a resource-based view in ensuring business sustainability among female microenterprise entrepreneurs.…”
Section: Literature Review and Hypothesis Development 21 Theoretical ...mentioning
confidence: 99%
“…Organizations with a strong green intellectual capital may be more likely to develop and implement sustainable practices and products (Zhu et al, 2005). A study by Liu et al (2022) found that green intellectual capital positively affects organizational innovation in the green technology industry, leading to improved organizational performance. The study found that green intellectual capital positively impacts green innovation in manufacturing companies, leading to increased market competitiveness.…”
Section: Importance Of Green Intellectual Capital In Corporate Worldmentioning
confidence: 99%
“…From the perspective of GSCI, existing research generally divides it into internal and external integration. Internal integration refers to the collaboration of all functional departments within an enterprise to form a cohesive unit, while external integration refers to the integration of the enterprise with external organizations (upstream and downstream partners) (Liu et al, 2022). Research on the relationship between GSCI and enterprise performance has yielded mixed results.…”
Section: Green Supply Chain Integrationmentioning
confidence: 99%